Hearing support system using environment sensor network - Ishi, Carlos T.; Chaoran Liu; Even, Jani; Hagita, Norihiro (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2016)
In order to solve the problems of current hearing aid devices, we make use of environment sensor network, and propose a hearing support system, where individual target and anti-target sound sources in the environment can be selected, and spatial information of the target sound sources is reconstructed. The performance of the selective sound separation module was evaluated for different noise conditions. Results showed that signal-to-noise ratios of around 15dB could be achieved by the proposed system for a 65dB babble noise plus directional music noise condition. In the same noise condition, subjective intelligibility tests were conducted, and an improvement of 65 to 90% word intelligibility rates could be achieved by using the proposed hearing support system.